(untitled) (Zaporizhzhia Historical Review, 2021)
The article illuminated the unknown pages of the post war history in the south of Ukraine to the wide circle of public ñ the return of population from evacuation and special settlements in 1944-1946. It is demonstrated who was the organizer of this action, how was this process of migration arranged, which consequences it had. These and other issues are considered on the bases of new archive materials which is introduced into the scientific turn over for the first time.